(untitled) (European Journal of Interdisciplinary Research and Development, 2022)
In this article, we talked about the importance of pea crop rotation in increasing yield and increasing soil fertility. Currently, the importance of leguminous grain crops in increasing soil fertility is incomparable due to the low content of humus and nitrogen in the soils of dry areas in various regions of Uzbekistan. As a result of the increase in the amount of organic matter in the soil after leguminous crops, the water-physical properties of the soil are improved. Therefore, the demand for legumes is increasing day by day.